Contemporary criminological issues: moving beyond insecurity and exclusion - Côté-Lussier, Carolyn; Moffette, David; Piché, Justin (University of Ottawa Press, 2020)
"This book examines key contemporary criminological issues with the aim of moving beyond scholarship that reproduces insecurity and exclusion. The edited collection features two tomes, one in English and one in French, reflecting interdisciplinary and critical criminological scholarship that advances alternative ways of conceptualizing and responding to criminalized activities and social harms.The breadth of the approaches characterizes much of critical criminological scholarship today, despite the growth of managerial and administrative criminologies and the rise of explicitly exclusionary and punitive state policies and practices with respect to ‘crime’ and ‘security.’ The book advances cutting-edge theories and methods to make sense of these issues, and proposes policy responses that promote social inclusion and security. Chapters are the result of collaborations by University of Ottawa researchers, along with their current or former co-researchers working in other disciplines or in other universities to highlight the array of networks and global reach of the department, and of past or present students."--